Reducing Emissions From Degraded Floodplain Wetlands - Limpert, Katy E.; Carnell, Paul E.; Trevathan-Tackett, Stacey M.; Macreadie, Peter I. (Frontiers in Environmental Science, 2020)
Freshwater wetlands are significant carbon sinks, however, altering a wetland’s hydrology can reduce its ability to sequester carbon and may lead to the release of previously stored soil carbon. Rehabilitating a wetland’s water table has the potential to restore the natural process of wetland soil carbon sequestration and storage. Further, little is known about the role of microbial communities that mediate carbon cycling during wetland rehabilitation practices. Here, we examined the carbon emissions and microbial community diversity during a wetland rehabilitation process known as ‘environmental watering’ (rewetting) in an Australian, semi-arid freshwater floodplain wetland. By monitoring carbon dioxide (CO2) and methane (CH4) emissions during dry and wet phases of an environmental watering event, we determined that adding water to a degraded semi-arid floodplain wetland reduces carbon emissions by 28-84%. The watering event increased anoxic levels and plant growth in the aquatic zone of the wetland, which may correlate with lower carbon emissions during and after environmental watering due to lower anaerobic microbial decomposition processes and higher CO2 sequestration by vegetation. During the watering event, areas with higher inundation had lower CO2 emissions (5.15 ± 2.50 g CO2 m-2 d-1) compared to fringe areas surrounding the wetland (11.89 ± 4.25 g CO2 m-2 d-1). CH4 flux was inversely correlated with CO2 emissions during inundation periods, showing a 38% (0.013 ± 0.061 g CO2-e m-2 d-1) increase when water was present in the wetland. During the dry phases of environmental watering, there was CH4 uptake within the fringe and aquatic zones (-0.013 ± 0.063 g CO2-e m-2 d-1). A clear succession of soil microbial community was observed during the dry-wet phases of the environmental watering process. This suggests that wetland hydrology plays a large role in the microbial community structure of these wetland ecosystems, and is consequently linked to CO2 and CH4 emissions. Overall, the total carbon emissions (CO2 + CH4) were reduced within the wetland during and after the environmental watering event, due to increasing vegetative growth and subsequent CO2 sequestration. We recommend environmental watering practices in this degraded arid wetland ecosystem to improve conditions for wetland carbon sequestration and storage.